Spontaneously Diabetic Torii Fatty Rat Shows Early Stage of Diabetic Retinopathy Characterized by Capillary Changes and Inflammation - Kasumi Kikuchi; Miyuki Murata; Yasushi Kageyama; Masami Shinohara; Tomohiko Sasase; Kousuke Noda; Susumu Ishida (Journal of Diabetes Research)
Conclusions: Our study demonstrated that the SDT fatty rats exhibited early diabetic retinal changes, suggesting that the SDT fatty rats may be useful in research on the pathogenesis of early human diabetic retinopathy.